A comparison of the NEIVFQ25 and GQL-15 questionnaires in Nigerian glaucoma patients - Mbadugha CA (Dove Medical Press, 2012)
Chigozie A Mbadugha, Adeola O Onakoya, Olufisayo T Aribaba, Folashade B AkinsolaGuinness Eye Centre, Department of Ophthalmology, Lagos University Teaching Hospital, Lagos State, NigeriaAim: To compare two vision-specific quality of life (QOL) instruments – the disease-specific 15-item Glaucoma Quality of Life questionnaire (GQL-15) and the nonglaucoma-specific 25-item National Eye Institute Visual Function Questionnaire (NEIVFQ25).Methods: The QOL of 132 glaucoma patients being managed in Lagos University Teaching Hospital and an equal number of controls matched for age and sex was assessed using two vision-specific instruments: GQL-15 and the NEIVFQ25. The categorization of the severity of glaucoma into mild, moderate, and severe disease was determined using the degree of visual field loss. The Statistical Package for the Social Sciences (version 15; SPSS Inc, Chicago, IL) software program was used for analyzing the data obtained. Spearman’s correlation coefficients were used to assess the correlation between the scores from the two questionnaires.Results: Patients had the greatest difficulty with activities affected by glare and dark adaptation in the GQL-15. Driving and general vision were the factors most affected in the NEIVFQ25. The Spearman rho values showed strong correlations (rho > 0.55) between the NEIVFQ25 and GQL-15 QOL scores for the total number of participants (rho: –0.75), total number of cases (rho: –0.83), and the mild (rho: –0.76), moderate (rho: –0.75), and severe (rho: –0.84) cases. There was a moderate correlation (rho: –0.38) for QOL scores of controls. Cronbach’s alpha was 0.94 for the GQL-15 and 0.93 for the NEIVFQ25, showing high internal consistency for both questionnaires.Conclusion: The GQL-15 and the NEIVFQ25 questionnaires showed high internal consistency, correlated strongly with each other, and were reliable in the assessment of glaucoma patients in this study.Keywords: primary open-angle glaucoma, quality of life questionnaires, GQL-15, NEIVFQ25